Chemistry - Chang, Raymond (McGraw-Hill, 2013)
Chang's best-selling general chemistry textbook takes a traditional approach and is often considered a student and teacher favorite. The book features a straightforward, clear writing style and proven problem-solving strategies. It continues the tradition of providing a firm foundation in chemical concepts and principles while presenting a broad range of topics in a clear, concise manner.